The role of social motivation and sociability of gamers in online game addiction - Lukas Blinka; Jakub Mikuška (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2014)
Massively multiplayer online (MMO) games represent a long-standing, intensive and wide spread type of online applications whose popularity continues to grow. Although just a mere entertainment and leisure activity for most gamers, its potentially negative and addictive outcomes were intensively studied and recently also acknowledged by the American Psychiatric Association (2013). MMOs are essentially a social activity, but empirical studies are equivocal in identifying whether and to what extent the social factors help develop the addictive gaming habits associated with these applications. The present study seeks to directly identify the role of social factors in online addictive gaming. Survey data from 667 MMO gamers were analysed. Together with an online game addiction scale, the investigated psychological factors included social motivation for gaming, online peer attachment and social self-efficacy. The results revealed that although social motivation was a predictor of addictive gaming, high social motivation was typical for intensive gamers regardless of their level of addiction. However, gamers at-risk of addiction scored lower in their social self-efficacy and interpersonal trust measured by peer attachment. This supports the poor-get-poorer hypothesis, that generally less socially skilled gamers face further problems online. However, social factors were only modestly associated to online addictive gaming which indicates higher relevance of other factors identified by literature, e.g. immersion and in-game rewards systems.